Environmental Science & Technology - Environmental Science & Technology (American Chemical Society, 2026)
Environmental Science & Technology reports impactful, groundbreaking, world-class research across a diverse range of environmentally relevant topics.
FI 1.56
Q1
Keywords: Earth; Space & Environmental Sciences; Environmental Science; Ciencia ambiental; Acuerdos transformativos; Transformative agreements; Biogeoquímica y biotecnología ambiental; Contaminantes en agua, suelo y aire: ocurrencia, destino, transporte y tratamiento; Ecotoxicología, salud pública, energía, clima y sistemas sostenibles